THE UTILIZATION OF LOCAL FOLKLORE AS TEACHING MATERIAL - Maman Rukmana (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2014)
Some discourses deal with folklore are presented by the authors of elementary school books for students. Unfortunately, the folklore presented does not considerate the level of meaningfulness for the elementary students. That is, the author forgets that the contextual material would have a higher significance level than the material in the form of folklore that is never recognized by the students. The problems in this paper are the criteria, and steps to arrange teaching material by using local folklore. The aims of this paper are to describe, and how to arrange language and Indonesian literature teaching materials source from the south Banten folklore for elementary school students in Pandeglang district. The method of this research is descriptive-analysis. Questionnaire technique is used to capture the teachers' opinion about the criteria and steps to make folklore as teaching materials. Folklore teaching materials of South Banten has fulfilled adequate criteria and considered the steps in arranging teaching materials. In the end to anticipate the limited teaching materials in the form of folklore from own region, the language and Indonesian literature teachers at an elementary school in Pandeglang can utilize it as an alternative and variety of teaching material.